The spatiotemporal dynamics of inhibition of return: evidence from computational modelling and human electrophysiology - Lim, Alfred C. K. (2019)
Inhibition of return (IOR) refers to an orienting mechanism that biases attention against returning to a previously attended location and has frequently been studied with the use of Posner’s cue-target paradigm (Posner & Cohen, 1984). Despite numerous studies that have examined many aspects of IOR, the neurophysiological mechanisms underlying IOR are still in dispute. Based on neurophysiological, behavioural, and neuroimaging data, it has been proposed IOR effects are related to different neural mechanisms and are implemented under different circumstances, and these other mechanisms may not be referred to as IOR. Behavioural inhibitory cueing effects (ICEs) are thought to be the result of multiple inhibitory cueing mechanisms – namely sensory adaptation (SA) and direct inhibition (DI). SA biases attention by attenuating the subsequent exogenous activity from an attended location, whereas late output-based DI inhibits oculomotor responses to an attended location. Simulations of inhibitory cueing mechanisms using a dynamic neural field (DNF) model of the intermediate layers of the superior colliculus (iSC) further suggest that such typical delayed behavioural responses to previously attended locations can be attributed to SA and DI. The goal of the present work was to explore the notion of multiple inhibitory mechanisms.